Advokasi Kebijakan Penghapusan Biaya Pemeliharaan Paten pada Entrepreneurial University - Ima Mayasari (Badan Strategi Kebijakan Hukum, 2023)
Advocating for the ellimination of patent maintanance feees in Higher Education, especially for Entrepreneurial Universities (EU), is essential. The number of patents is the primary indicator in determining the most innovative university. Therefore, the Minister of Law and Human Rights in 2020 adapted by issuing Permenkumham 20/2020 concerning Requirements and Procedures for Imposing Certain Tariffs on Patent and Copyright. According to Permenkumham 20/2020, in some instances, tariffs on patent services can be imposed in the amount of zero rupiahs, including for Higher Education. The research problem is How to advocate for a policy to eliminate patent maintenance fees at an EU?. This research aims to analyze Policy Advocacy for the Elimination of Patent Maintenance Fees at EU. This study uses the Advocacy Strategy Framework concept proposed by Coffman. The research employs a qualitative research method. The results of the research show that the Advocacy Strategy Framework regarding the Elimination of Patent Maintenance Costs in Permenkumham Number 20/2020 is carried out through three changes, Awareness, Will, and Action carried out to audiences, namely Public and Influencers; Influencers; Influencers and Decision Makers; and Decision Makers. The researcher recommends to the Ministry of Law to compile a Roadmap and Action Plan regarding Elimination of Patent Maintenance Costs in Policy Products in the form of Ministerial Decrees Law and Human Rights or Decision of the Director General of IP regarding the Roadmap and/or Action Plan regarding this matter.